2014
DOI: 10.5901/mjss.2014.v5n13p100
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecure Household Coping Strategies: The Case of a Low Income Neighborhood in South Africa

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 14 publications
(15 reference statements)
5
9
0
Order By: Relevance
“…However, from a broader human development perspective, the impact of education on sustainability indicators goes far beyond, it contributes to the social, political as well as the cultural environment, which can have fundamental influence on the access and utilization of basic resources [25]. This finding is also in line with other studies done in Ethiopia and South Africa [26,27]. Moreover, in their cross country analysis, De Muro and Burrch (2007) [25] of the FAO suggested that primary education was a crucial element in reducing food insecurity in rural areas compared to other factors such as access to water, health, and sanitation [25].…”
Section: Discussionsupporting
confidence: 82%
“…However, from a broader human development perspective, the impact of education on sustainability indicators goes far beyond, it contributes to the social, political as well as the cultural environment, which can have fundamental influence on the access and utilization of basic resources [25]. This finding is also in line with other studies done in Ethiopia and South Africa [26,27]. Moreover, in their cross country analysis, De Muro and Burrch (2007) [25] of the FAO suggested that primary education was a crucial element in reducing food insecurity in rural areas compared to other factors such as access to water, health, and sanitation [25].…”
Section: Discussionsupporting
confidence: 82%
“…The Jumla case confirms the findings of studies undertaken elsewhere (see Chambers and Conway 1992;Ford and Beaumier 2011;Grobler 2014;Osbahr et al 2008) that consumption rationing is one measure that people in a food crisis adopt routinely. As mentioned earlier, people may be aware of but unable to avoid the long-term negative consequences of particular strategies.…”
Section: Withdrawingsupporting
confidence: 88%
“…In the research Ngidi and Hendriks [32] performed at Jozini, a rural Municipality in South Africa, they found that relying on less preferred and/or inexpensive food was the most commonly employed strategy (88.4%)-followed by borrowing food or money for food and begging from friends or relatives for food (85.5%, in both). Grobler [37] found in Bophelong, a low-income neighborhood in South Africa, that the coping strategies used by most of the households in the sample is relying on less expensive commodities, followed by buying only necessities, sticking to budget, limiting portions and skipping meals. For their part, the work of Chagomoka et al [38], carried out in Ghana, pointed out that households used coping strategies more frequently, such as skipping meals the whole day, borrowing food or money to buy food, consuming seed stock and purchasing food on credit.…”
Section: Discussionmentioning
confidence: 99%